Topological Design of a Mortar Base Plate under Impact Loads - Fengfeng Wang; Guolai Yang (Shock and Vibration)
In this work, the topology optimization of a mortar base plate is analysed under impact loading conditions. Usually, in this case, only ordinary topology optimization under volume constraints is considered. However, to reduce the quality of the mortar base plate and facilitate engineering applications, the topological optimization problem of the continuum of the base plate under the engineering and quality constraint is considered. A finite element model has been established and verified by testing for the mortar base plate. The variable density method was used to obtain the topological optimization results of the base plate based on the force transmission path, and then the structure was reconstructed. The mass of the optimization model of the base plate is 12.78% lower than that of the original model. In comparison with the original base plate before optimization, the results show that the maximum deformation and stress of the base plate decreased by 16.85% and 35.52%, respectively. Also, the firing stability of the mortar meets requirements, which not only meet the design requirement but also provide a reference for the performance improvement and structural optimization design of the base plate.